Merekonstruksi Kesetaraan Gender dalam Hukum Keluarga: Analisis Normatif dan Komparatif Sistem Hukum Keluarga Eropa dalam Konteks Keagamaan - Viktoriia Kobko -Odarii; Yuliia Leheza; Konstantin Sokolovskiy; Halyna Tatarenko; Oleksandra Nestertsova -Sobakar (Syariah: Jurnal Hukum dan Pemikiran, 2025)
This study examines the normative and doctrinal foundations of gender equality in European family law and investigates how Christian and Islamic religious heritage continues to shape contemporary legal interpretations and outcomes. Using a multi-method designcombining normative legal analysis, cross-jurisdictional comparison, and qualitative assessment of statutory frameworks, case law, and scholarly literature, the study evaluates legal mechanisms regulating gender relations through the lenses of critical gender theory, intersectional analysis, and religious ethics. The findings reveal marked divergences in matrimonial property regimes, valuation of care work, and principles governing divorce. Despite widespread recognition of formal equality, substantive inequalities remain embedded due to the undervaluation of domestic labor, tensions between autonomy and compensation principles, and the persistence of cultural â€œcryptotypesâ€ rooted in religious and historical traditions. The analysis demonstrates that Christian and Islamic heritages exert dual influences: they reinforce patriarchal norms while simultaneously offering internal interpretive pathways for gender-progressive reform. The results underscore that, although European family law systems show increasing convergence toward human rights standards, doctrinal inconsistencies and implicit judicial biases continue to limit equitable outcomes. The study proposes a reconstructed model of family law incorporating gender-sensitive jurisprudence, equitable valuation of non-financial contributions, stronger regulation of religious adjudicatory bodies, and gender-responsive judicial training. This research contributes conceptual clarity and policy-relevant insights into how family law can be restructured to advance substantive gender equality within Europeâ€™s diverse socio-legal contexts.